A Rare Case of Cerebrotendinous Xanthomatosis Associated With a Mutation on COG8 Gene - Hamed Ghoshouni MD; Roham Sarmadian MD; Rana Irilouzadian MD; Habibe Nejad Biglari MD; Abolfazl Gilani MD (SAGE Publishing, 2023)
Cerebrotendinous xanthomatosis ( CTX ) is a rare hereditary disease described by a mutation in the CYP27A1 gene , which encodes the sterol 27-hydroxylase enzyme involved in the synthesis of bile acid. Accumulation of cholesterol and its metabolite, cholestanol, in multiple body organs causes the symptoms of this disease. In addition, a mutation in the COG8 gene , which encodes a subunit of conserved oligomeric Golgi (COG) complex, causes another rare disorder attributed to type IIh of congenital disorder of glycosylation ( CDG ). We described a rare case of CTX disorder associated with a mutation on COG8 gene , which presented by unusual symptoms.